Determinant physical factors in the wheelchair tennis player - Sánchez-Pay, A. (Coaching and Sport Science Review, 2021)
The objective of this research was to identify the most determining physical factors in the ranking position of wheelchair tennis players (WT). In a national camp, the nine best nationally ranked Spanish male WT players (38.35 ± 11.28 years, 63.77 ± 7.01 kg. weight) completed a test battery. Significantly higher correlations were observed in medicine ball throws, 5 and 20-metres sprints with racquet and in an agility test without racquet. In addition, the regression analysis identified two predictor models of the player's ranking position that included both the serve throw and the 5-metre racquet sprint. In conclusion, it is recommended that coaches and physical trainers include in their training programmes medicine ball exercises as well as acceleration drills over short distances.